Evaluation of the antimicrobial and cytotoxic effect of Dendranthemaindicum (L Desmoul ) leave extract - H, Momoh,; M.M, Idris; O.A, Adoum, (IJRDO-Journal of Applied Science, 2017)
Hexane, chloroform, ethyl acetate and ethanol extracts of Dendranthema indicum leaf werestudied for their cytotoxic effect and antimicrobial activities against seven human pathogenicbacteria Shigella dysenteriae, Salmonella typhi, klebsiella pneumonia, Staphylococcus aureus,proteus mirabilis, Escericia coli and pseudomonas aeriginosa,) using disc diffusion method.All the extracts exhibited moderate to good antibacterial activity against all the pathogenstested except proteus mirabilis and Salmonella typhi, The chloroform extract exhibited thelargest zone of inhibition (20 mm) against Staphylococcus aureus.The ethyl acetate extractsexhibited the highest lethality on brine shrimp larvae at LC 50 values 211.6. (LC 50 ) weredetermined at 95% confidence intervals by analyzing the data on a computer loaded with“Finney Programme.”